Kualitas Pelayanan Administrasi Kependudukan melalui Aplikasi Bedas Digital Services di Kantor Kecamatan Margahayu Kabupaten Bandung - Prayoga, Indra Aditya; Nurajizah, Shifa (PROPAGANDA, 2025)
This study discusses the quality of population administration services based on the Bedas Digital Services application in Margahayu District, Bandung Regency, which is considered to be suboptimal. The purpose of this study is to analyze service quality from the aspects of usability, information quality, and service interaction quality based on Barnes and Vidgen's theory. This study uses a descriptive qualitative method with informants from district officials, application operators, and service users. The results indicate that the application is relatively easy to access, but there are still challenges in understanding the service workflow, particularly for individuals with low digital literacy. The information in the application is relatively complete, but there are still shortcomings in data accuracy and updates. Service interaction is fairly good, but staff responses are still limited. The main obstacles are insufficient socialization, technical challenges, and low digital literacy. The subdistrict government has conducted education programs, enhanced operator capacity, and maintained the application. The study recommends improving digital literacy, optimizing application features, and implementing better feedback mechanisms.